Vienna’s Resistance to the “Neoliberal Turn" - Florian Urban (Footprint)
At the turn of the twenty-first century, when public authorities all over Europe increasingly retreated from their responsibility for housing, Vienna refrained from large-scale privatisations. Upholding the system of state-subsidised housing, the Austrian capital supported new architecture as a means to regenerate the inner city and to promote innovative social policy. This was based on original design inspired by a variety of mostly modernist precedents. Examples for new residences that follow this strategy include the Car-free Model Estate (1996–99, Cornelia Schindler and Rudolf Szedenik), the women-led scheme Margarete Schütte-Lihotzky-Hof (1993–97, Liselotte Peretti, Gisela Podreka, Elsa Prochazka and Franziska Ullmann), and the residences on the former railway station Nordbahnhof (1992–2015, master plan by Boris Podrecca and Heinz Tesar, buildings by various architects). This article will present Vienna’s turn-of-the-twenty-first-century housing as a successful strategy to provide affordable residences that respond to current needs, and at the same time a way to harness innovative architecture for social policy goals. The Vienna case also suggests that the ‘neoliberal turn’ in housing provision was a matter of political choice rather than economic necessity.